Creating a tobacco line with a weaker antifeedant property against colorado potato beetle - N. E. Kostina; A. V. Spaselnikova; A. A. Egorova; E. V. Kolosovskaya; D. V. Domrachev; A. V. Romanova; S. R. Tumanyan; S. Chamas; J. Kumlehn; I. M. Dubovskiy; S. V. Gerasimova (Биотехнология и селекция растений, 2020)
Background. Genetic modification of plants is one of the promising strategies to increase their resistance to insect pests. The development of metabolic or RNA interference systems for plant protection requires appropriate models of host-insect interactions. Nicotiana tabacum L. is a classical model plant used in molecular and metabolic engineering. We consider tobacco as a model for developing protective strategies against Colorado potato beetle (Leptinotarsa decemlineata Say, CPB). Normally, tobacco is toxic for CPB due to high content of nicotine and related alkaloids in leaves. Modification of the tobacco genome could provide tobacco genotypes with altered metabolism suitable for CPB feeding. It is known that different mutations in Berberine Bridge-Like (BBL) genes cause different alterations in tobacco leaf alkaloid levels. In the current study, the Cas9/gRNA system targeting members of the BBL gene family of tobacco was used to create a line which can serve as a diet for CPB. Results. In order to obtain tobacco with modified alkaloid content, two gRNAs matching target sequences in six BBL genes were selected. Each gRNA was cloned into a gRNA/Cas9 generic vector. The created constructs were mixed and used for biolistic transformation of tobacco leaf explants together with the pBI121 plasmid harboring the kanamycin resistance gene nptII and the reporter E.coli betaglucuronidase (GUS) gene. Regenerants were selected on 100 mg/l of kanamycin and checked for transgene presence by histochemical GUS-assay. Unexpectedly, the regenerated plants displayed a variety of adverse phenotypic effects including different degree of growth and rooting inhibition, early flowering, increased number of internodes, changes in leaf shape, fusion of flowers, longostyly, and partial sterility. Only one from seven obtained calli produced a population of regenerated plants without severe phenotypic abnormalities. The NtaBBL5-14 line of clonally propagated plants was selected from this population and used for a CPB feeding experiment. It was shown that CPB larvae consume the leaves of NtaBBL5-14 line ten times more efficiently than the leaves of control plants (97±0.5% vs. 9±3% in 24 h respectively). Conclusion. The NtaBBL5-14 tobacco line is suitable for CPB feeding and can be further used as a model for studies in plant-pest interaction. The modification of other genes regulating nicotine metabolism can be a promising strategy to obtain tobacco plants edible for CPB with less pleiotropic effects.